Pengaruh Promosi Layanan Online Melalui Media Sosial Instagram terhadap Kepuasan Anggota Perpustakaan Nasional - Boby Saputra; Zulfebriges (Bandung Conference Series: Communication Management, 2022)
Abstract. This study aims to determine how much influence the promotion of online services through social media Instagram on the satisfaction of members of the National Library of Indonesia. Identification of problems include: 1) How much influence does the contents of the Instagram product content of the National Library of Indonesia (@perpusnas) have on the satisfaction of the members of the RI Library, 2) How much influence is the function of sharing videos and photos of Instagram products of the National Library of Indonesia (@perpusnas) on the satisfaction of Library Members RI, 3) How big is the effect of suppressing the promotional costs of the National Library of Indonesia Instagram products (@perpusnas) on the satisfaction of members of the RI Library. To see the quality of Instagram social media as a promotional tool, researchers used Lim & Yazdanifard's theory, namely the Instagram social media indicator. Meanwhile, to assess the satisfaction of the library members, researchers used the theory of Fransisca Rahayuningsi, namely measuring visitor satisfaction. This research was conducted at the National Library of Indonesia, Jln. Salemba Raya Bo. 28a, Jakarta, tel. 085717147303 Central Jakarta 10430. The object of this research is the Instagram followers of the National Library of Indonesia (@ Perpusnas.go.id) to determine the effect of online social media service promotion Instagram on the satisfaction of members of the National Library of Indonesia. The research method used is the associative method, because the associative research method aims to find the relationship between a variable and other variables and how the strength of the relationship is. The technique of collecting data from this research is through literature study and questionnaires. The sampling technique used a sampling technique using a cluster sampling technique (area sampling). The number of samples in this study based on the cluster sampling technique (area sampling) was 150 followers. The data processing techniques of this study are correlation and regression. Based on the data analysis that has been done, it can be concluded that the percentage of the contribution of the influence of the independent variable, namely the promotion of social media Instagram on the dependent variable, namely member satisfaction is 46.5%. While the remaining 53.5% is influenced by other factors not examined by researchers. So it can be concluded that there is an effect of Instagram social media promotion on member satisfaction. Abstrak. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh promosoi layanan online melalui media sosial instagram terhadap kepuasan anggota Perpustakaan Nasional RI. Identifikasi masalah antara lain: 1) Seberapa besar pengaruh isi konten produk instagram Perpustakaan Nasional RI (@perpusnas) terhadap kepuasan Anggota Perpustakaan RI, 2) Seberapa besar pengaruh fungsih berbagi video dan foto produk instagram Perpustakaan Nasional RI (@perpusnas) terhadap kepuasan Anggota Perpustakaan RI, 3) Seberapa besar pengaruh penekanan biaya promosi produk instagram Perpustakaan Nasional RI (@perpusnas) terhadap kepuasan Anggota Perpustakaan RI. Untuk melihat kualitas media sosial Instagram sebagai alat promosi peneliti mengunakan teori dari Lim & Yazdanifard yaitu indikator media sosial Instagram. Sedangkan untuk menilai kepuasan anggota perpustakaan peneliti menggunakan teorti dari Fransisca Rahayuningsi yaitu mengukur kepuasan pemustaka. Penelitian ini dilakukan di Perpustakaan Nasional RI, Jln. Salemba Raya Bo. 28a, Jakarta, telp. 085717147303 Jakarta Pusat 10430. Objek dalam penelitian ini adalah followers Instagram Perpustakaan Nasional RI (@Perpusnas.go.id) guna mengetahui pengaruh promosi layanan online media sosial Instagram terhadap kepuasaan anggota Perpustakaan Nasional RI. Metode penelitian yang digunakan adalah metode metode asosiatif, karena metode penelitian asosiatif bertujuan untuk mencari kaitan suatu variabel dengan variabel lain serta bagaimana tingkat kekuatan hubungannya. Teknik pengumpulan data dari penelitian ini melalui studi kepustakaan dan angket. Teknik pengambilan sampel menggunakan teknik sampling dengan menggunakan teknik claster sampling (area sampling). Jumlah sampel dalam penelitian ini berdasarkan teknik claster sampling (area sampling) adalah sejumlah 150 followers. Teknik pengolahan data dari penelitian ini berupa korelasi dan regresi. Berdasarkan analisa data yang sudah lakukan, maka diperoleh kesimpulan bahwa presentase sumbangan pengaruh variabel independen yaitu promosi media sosial instagram terhadap variabel dependen yaitu kepuasan anggota sebesar 46,5%. Sedangkan sisanya sebesar 53,5% dipengaruhi oleh faktor-faktor lain yang tidak diteliti oleh peneliti. Jadi disimpulkan terdapat pengaruh prmosi media sosial Instagram terhadap kepuasan anggota.